A Cross Sectional Survey of Knowledge, Attitude and Practice of Antibiotic Use in Pregnancy Patients Among Undergraduate Students in Dental School - Mabbithasri. A , Dr. Subasree S (South Eastern European Journal of Public Health, 2025)
Objective: Antibiotics were “invented” billions of years ago and susceptibility is largely the product of bacterial adaptation to aeons of antibiotic exposure. Because of antibiotics' curative ability, their use in nature usually selects for pre-existing resistant bacteria populations. Antibiotics are the medications that are commonly prescribed for pregnant women. Antibiotics play a vital role in improving and enhancing the health of pregnant women. Materials and Methods: An online survey was conducted through google docs link. A questionnaire containing 18 questions was created and the questions were approved by Saveetha research board Chennai. Discussion: Dentist usually have a separate treatment plan for pregnant women as they too fear anesthesia, analgesics and some antibiotics which can lead to malformations. In a study conducted by tantradi et al, among interns, 35% of the participants had never treated a pregnant patient, 57 % had treated fewer than 5 pregnant patients, and 21% of the participants were not confident in treating such patients. Conclusion: Dental treatment for pregnant women needs special care and attention. From the results obtained it is known that the dental students have average knowledge about the use of antibiotics for pregnant women.